Understanding Intellectual Capital, Corporate Entrepreneurship and Firm Performance of Small and Medium Enterprises (SMEs) in Malaysian Tourism Industry / Ahmad Rusydan Ab Kadir, Rohana Ngah, Zarina Salleh - Ab Kadir, Ahmad Rusydan; Ngah, Rohana; Salleh, Zarina (2021)
SMEs' performance in the tourism industry is essential for countries like Malaysia, as it is one of the main contributors to the country's economic growth and job creation. Previous studies showed that SMEs in the tourism industry lack creativity and innovation in providing products and services for tourists as well as offering only basic products and services resulting in lower spending hence, lower performance. One of the ways to mitigate these drawbacks is to encourage SMEs to identify, manage and capitalize on their limited intangible resources, entrepreneurial activities and processes to enhance firm performance. The general objective of this study is to investigate how SMEs in the tourism industry in Malaysia can improve their business performance with intangible resources such as intellectual capital and corporate entrepreneurship. This study used an online survey for data collection collected from SMEs involved in the tourism industry nationwide. A total of 158 respondents were selected using a simple random sampling technique. Respondents were asked about their internal resources such as intellectual capital, entrepreneurial activities and processes such as innovation, strategic renewal and corporate venturing, as well as their financial and non-financial performance. The data was analysed using Partial Least Square – Structural Equation Modelling (PLS-SEM) to examine the relationship of intellectual capital and corporate entrepreneurship on the performance of SMEs in the tourism industry. The findings suggested that SMEs especially in the tourism industry are to identify and capitalise on their internal resources and entrepreneurial activities in favour of improved performance.